KEANEKARAGAMAN JENIS DAN KEPADATAN BURUNG DIURNAL PADA KAWASAN WISATA ALAM RESORT BELABAN SPTN WILAYAH I NANGA PINOH TNBBBR - Anwari, M Sofwan; Riko, Eryesiswanto; Nurhaida, Nurhaida; Purwano, Sigit (Universitas Tanjungpura, 2023)
Birds are wild animals that have an important role in human life both in terms of economics, tourism, education, and science. Belaban Resort is a conservation area designated as a tourist attraction and research location. This research aims to examine the diversity of species and diurnal density of birds in the Belaban SPTN Resort natural tourism area, region I Nanga Pinoh, Bukit Baka Bukit Raya National Park. The method used is the IPA (Indices Ponctuels d'Abondance) method, where the data collection technique uses a combination of paths with point counting. The number of diurnal bird species in the natural tourist area of Belaban SPTN Resort Region I Nanga Pinoh, Bukit Baka Bukit Raya National Park was found of the 41 types of diurnal birds from 28 tribes (families) spread across km 37, 28 species were found with a total of 167 individuals, while at km 39 there were 17 species found with a total of 96 individual birds. The results of the diversity index calculation show a moderate level of species diversity with diversity index values of 1.41 (Km 37) and 1.20 (Km 39), while individual density falls into medium density with density values of 33.3 (Km 37) and 19.2 (Km 39).Keywords: Birds, Resort Belaban, Species Diversity and Density.AbstrakBurung merupakan satwa liar yang memiliki peran penting dalam kehidupan manusia baik ditinjau dari segi ekonomi, pariwisata, pendidikan dan ilmu pengetahuan. Resort Belaban merupakan sebuah kawasan konservasi yang diperuntukan sebagai tempat wisata dan lokasi penelitian. Tujuan penelitian ini untuk mengkaji keanekaragaman jenis dan kepadatan burung diurnal pada kawasan wisata alam Resort Belaban SPTN wilayah I Nanga Pinoh Taman Nasional Bukit Baka Bukit Raya. Metode yang digunakan adalah metode IPA (Indices Ponctuels d'Abondance), dimana Teknik pengambilan data menggunakan kombinasi jalur dengan point count, Jumlah jenis burung diurnal yang ada pada kawasan wisata alam Resort Belaban SPTN Wilayah I Nanga Pinoh, Taman Nasional Bukit Baka Bukit Raya ditemukan 41 jenis burung diurnal dari 28 suku (famili) yang tersebar di km 37 ditemui 28 jenis dengan jumlah individu sebanyak 167 individu, sedangkan pada km 39 ditemui sebanyak 17 jenis dengan jumlah individu sebanyak 96 individu burung. Hasil perhitungan indeks keanekaragaman menunjukan tingkat keanekaragaman jenis yang sedang dengan nilai indeks keanekaragaman 1,41 (Km 37) dan 1,20 (Km 39), sedangkan untuk kepadatan individu masuk kedalam kepadatan sedang dengan nilai kepadatan 33,3 (Km 37) dan 19,2 (Km 39).Kata Kunci : Burung, Resort Belaban, Keanekaragaman Jenis Dan Kepadatan